Analisis Penurunan BOD dan Fosfat Limbah Laundry pada Free Floating Plant Wetland dengan Variasi Aerasi - Shinta Esharikha; Firra Rosariawari (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Laundry waste that comes from home laundry still often discharges its waste directly into water bodies. This can cause pollution because laundry waste contains quite a lot of pollutants such as phosphate and BOD derived from detergent raw materials used also come from dirt loss when washing clothes. Apu wood roots that are fibrous and have fine hair allow the growth of microorganisms in the rhizosphere that can degrade organic substances contained in waste, to then be absorbed by plants as nutrients. Aeration is also done to help meet the oxygen supply needed by microorganisms to be able to degrade pollutants contained in waste. The purpose of this study is to see the ability of apu wood plants to remove levels of pollutants, namely BOD and Phosphate, also to see which variations of aeration are best to help remove BOD and Phosphate levels contained in waste. From this study, the best results were obtained that the largest BOD removal was 85.71% on day 9 with full 24-hour aeration, and phosphate by 74% on day 9 with full 24-hour aeration.